HUBUNGAN ASPEK KOGNITIF TERHADAP PERILAKU PSN 5M PLUS PADA MASYARAKAT - Mudhofar, Muhamad Nor; Sinaga, Jernita; Lestaluhu, Kasman; Kurniawati, Lia (Ensiklopedia of Journal, 2025)
Abstract: Dengue Hemorrhagic Fever (DHF) is one of the infectious diseases that remains a public health issue in Indonesia. Based on the results of a preliminary survey conducted in Bandar Lampung City, it was found that Rajabasa District recorded the highest number of dengue hemorrhagic fever (DHF) cases compared to other districts. The objective of this study is to investigate the relationship between cognitive aspects and the behavior of the 5M Plus program among the community. The study design used in this research is cross-sectional. The research was conducted in July 2024 in the Rajabasa District. The population consists of all families residing in the Rajabasa District, totaling 10,101 families. The sample size was 115 families selected using Simple Random Sampling. The research instrument used a questionnaire. Data analysis was conducted using univariate and bivariate methods. The results of the study indicate a relationship between knowledge (p-value: 0.015) and attitude (p-value: 0.004) toward mosquito breeding site elimination (MBSE) behavior. It is recommended that the community recognize the signs and symptoms of dengue fever so that they can control vectors and reduce their numbers to achieve community health.Keywords: Knowledge, Attitude, Behavior.